The macroeconomy : a business perspective - Cuthbertson, Keith; Gripaios, Peter (London : International Thomson Business Press, 1997)
This book is about: Economic foundations; Schools of thought; Inflation; Risk and its impact on business; Exchange rates; ...
Keywords: Great Britain; Macroeconomics; Managerial economics; Managerial economics; Macroeconomics; Great Britain -- Economic conditions